Fodor's essential Norway 2023 - Gregersen, Ann-Mari; Hansen, Janicke; Pereira, Alexandra (Travel writer); Woolsey, Barbara (Fodor's travel guides., 2023)
Whether you want to kayak around the fjords, watch the northern lights, or explore new Nordic cuisine, the local Fodor's travel experts in Norway are here to help! Essential Norway, 1st Edition is part of the award-winning Fodor's Essential series recognized by Booklist as the "Best Travel Guide in 2019." This guidebook is packed with maps, carefully curated recommendations, and everything else you need to simplify your trip-planning process and make the most of your time. This BRAND-NEW Norway guide is designed with an easy-to-read layout, fresh information, and beautiful color photos.